Application studies for fatigue strength improvement of welded structures by high-frequency mechanical impact (HFMI) treatment. (1st January 2016) - Yıldırım, Halid Can; Leitner, Martin; Marquis, Gary B.; Stoschka, Michael; Barsoum, Zuheir
Graphical abstract: Highlights: HFMI-treated welded structures are presented with previously proposed design curves. 62 weld details of large-scale complex structures are extracted from the literature. Fatigue testing of 23 cover-plates is carried out for the use of crane industry. Proposed design curves based on f y are conservative with respect to fatigue data. Abstract: In 2013, a new guideline for the design of high-frequency mechanical impact (HFMI) treatment was drafted. The proposed design curves were made based on the fatigue data of axially-loaded welded joints which were manufactured from high-strength steels. All the S–N curves were shown to be conservative with respect to the existing fatigue data for laboratory-scale specimens of longitudinal, transverse, and butt welds. In reality, structures in civil, offshore, mechanical engineering and ship industries generally include large-scale and more complicated components rather than laboratory-scale specimens. Therefore, this paper firstly presents the validation of design proposals by considering fatigue data sets for large-scale welded structures. In total, 62 fatigue data points for bridge, crane and beam-like components are reported, in which the yield strength varies from 250 to 725 MPa, and stress ratio varies from −1 to 0.56. Validations are then extended also for cover plates by performing fatigue tests of 23 weld details both in as-welded and HFMI-treated cases for the use of crane industry. Both the extracted and obtained fatigue data are found to be in good agreement with the previously-proposed design guidelines for nominal and effective notch stress assessment.